南極湖泊沉積物中鈾釷系同位素及碳質物之來源與環境意義 - 方慧中; Fang, Hui-Chung (2015)
南極地區距離人類活動遙遠且少有人為汙染，因此比起其他地區相對單純，適合用以探討全球環境變遷。本研究藉由鈾釷系同位素與碳質物在南極湖泊沉積物岩芯L2-2中之變化，重建該地區之古環境變遷。由鉛-210定年結果表明，該地區擁有相較於其他副極地湖泊更高的沉積速率，這部分可能與湖泊面積大小、鄰近冰川與具有高度侵蝕作用有關，其中過剩鉛隨深度的變化反映著氣候上季節性的變化。而在鈾釷同位素示蹤風化過程的部分，結果表明該地區主要由物理風化主導，少數層位則明顯有相對強烈的化學風化過程。另外，傳統使用可反應環境中氧化還原變化的鈾-238，在本岩芯中並未有明顯變化趨勢。反觀以釷-228/釷-232活度比值而言，其誤差小且隨深度呈現明顯變化，指示著岩芯由表層至底層短短八年內經歷三次環境變化，這部分則是與短期氣候變化相關。更在此提出比起傳統使用之鈾-238，釷-228/釷-232活度比值反應更具代表性，同時也指示著該地區具有地下水的活動。本研究亦發現，前人文獻中指出同樣具備指示環境狀態能力的鈾-238與總有機碳隨深度變化趨勢並不相同，因此，本研究以溫度做為區別碳質物之來源與類型的依據，將碳質物區分為湖相與陸相有機碳、以及石墨質碳三大類，得到該區域主要由湖相來源之有機碳與無法指示環境氧化還原狀態之石墨質碳成分所主導，並發現單純以總有機碳值做為環境狀態指標並不具代表性，因此，有別於前人文獻，本研究提出一個新的環境狀態指標－TOC300，說明以該區域而言，對於指示環境氧化還原狀態具備代表性者，僅有300°C以下可被分解的有機碳，並且得到與釷同位素一致的氧化還原結果，同時發現TOC300有與過剩鉛類似的指數衰減情形，計算有機碳降解速率常數可得到有機碳在該地區的停留時間約僅有十年左右。 Continuous sediment accumulation in Antarctic lakes provides useful information on past environmental/climatic changes in polar region. To reconstruct such changes, a sediment core (L2-2) was collected from a lake basin in the Antarctica for the analysis of U- and Th-series isotopes and carbon contents. The measured excess 210Pb activities show a decreasing trend with depth, superimposed by about 7-8 cyclical changes through the core. The results give a mean sedimentation rate of ~4.681.81 cm/yr and a seasonal variability in excess 210Pb flux to the lake. Activity ratios of 234U/238U and 230Th/238U show an intense physical weathering in the study site proving the high sedimentation rate. Against conventional view, 238U activity do not show apparent variation through the core. On the contrary, 228Th/232Th ratios with lower errors and distinct variation indicates three times changes of redox conditions within 8 years which is related to precipitation and sea ice albedo. Different from previous researches, it is found in this study that 228Th/232Th ratio showed a more sensitive response in environmental redox conditions than conventional use of 238U. Against a typical view, we find no simple correlation between 238U activity and organic carbon content in core L2-2. Our study find out the ...